2018
DOI: 10.1002/bmb.21165
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an undergraduate laboratory activity exploring the dna analysis of pet food

Abstract: A novel experiment has been developed with a goal of enhancing engagement and deepening understanding of fundamental molecular biology concepts. In this laboratory activity, students investigate the composition of pet foods through quantitative polymerase chain reaction (qPCR) analysis. By conducting this experiment, students address a scientific question that has the potential to be of personal interest and they gain an appreciation of the power of genetic analysis. To develop this activity, ingredient lists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…An optional oral presentation may be included to allow students to explain how DNA barcoding can be used in other fields. 5,6 Instructors may wish to add another class, if students need additional instruction on how to prepare reports. We suggest to refer to our F I G U R E 6 BLAST alignment of the ITS sequence received by a student suggests the identity of the sample as Lentinula (shiitake mushroom was used for the experiment).…”
Section: Assessment Of Student Learning and Feedbackmentioning
confidence: 99%
See 3 more Smart Citations
“…An optional oral presentation may be included to allow students to explain how DNA barcoding can be used in other fields. 5,6 Instructors may wish to add another class, if students need additional instruction on how to prepare reports. We suggest to refer to our F I G U R E 6 BLAST alignment of the ITS sequence received by a student suggests the identity of the sample as Lentinula (shiitake mushroom was used for the experiment).…”
Section: Assessment Of Student Learning and Feedbackmentioning
confidence: 99%
“…An optional oral presentation may be included to allow students to explain how DNA barcoding can be used in other fields 5,6 . Instructors may wish to add another class, if students need additional instruction on how to prepare reports.…”
Section: Assessment Of Student Learning and Feedbackmentioning
confidence: 99%
See 2 more Smart Citations
“…As a particular case of active learning, research‐based learning (RBL) strategies have already been applied in many high‐level universities within a wide variety of fields, such as the social sciences, engineering, medicine, and geography . In particular, in the biology education context, they are an effective pedagogical strategy to promote student achievement and learning quality . Knutson et al reported how students achieved high levels of critical biochemical laboratory skills and critical thinking while increasing their confidence and motivation when working in a biochemical research‐based experience.…”
Section: Introductionmentioning
confidence: 99%